Clinicoradiological correlation in birth asphyxia - Patil, Basavaraj; Harshangi, Sandeep; Prabhu, Bhagya (International Journal of Research in Medical Sciences, 2017)
Background: Hypoxic Ischemic Encephalopathy (HIE) is the most dreaded neurological disease of the new-born. Assessment of severity of HIE would help proper parent counseling and early institution of stimulation therapy for better development of the infant. Methods: This study was conducted between December 2012 and May 2014. 37 term neonates with perinatal asphyxia were the subjects. The cranial ultrasound, EEG and MRI findings of these babies are analysed and correlated with each other and with clinical staging and the neurological condition of the babies at discharge. Results: Among the 37 neonates, 21 were of HIE stage 2 and 16 were of stage 3. Sensitivity of EEG in detecting abnormality in the neurological condition according to our study is 76.9%, specificity 87.5%, positive predictive value 76.9%, negative predictive value 87.5%. Sensitivity of severe pattern of injury in MRI brain in detecting abnormality in neurological condition according to our study is 76.9%, specificity 91.6%, positive predictive value 83.3%, negative predictive value 88%. Involvement of both basal ganglia and cortex in MRI brain had statistically significant correlation with abnormal neurological condition at discharge in our study (P = 0.04). Conclusion: An abnormal EEG and MRI brain in a term new-born with Hypoxic Ischemic Encephalopathy (HIE) is associated with poor neurological outcome. Involvement of basal ganglia/thalamus and cortex together in the MRI are predictors of abnormal outcome.